Pengaruh Profitabilitas, Leverage, dan Capital Intensity terhadap Tax Avoidance - Setyaningsih, Fitri; Nuryati, Tutty; Rossa, Elia; Marinda Machdar, Nera (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this research is to find and analyze the theory which mentions the effect of profitability, leverage, and capital intensity on tax avoidance. This study uses a literature review methodology. In this study, the researcher presents reasons, other explanatory variables, and findings from previous literature. The theory behind this research is agency theory and exchange theory. Mapping of other explanatory variables that affect tax evasion consists of profitability, leverage, and capital intensity. These results state that there is a different relationship between profitability, leverage, and capital intensity on tax avoidance so that no agreement has been reached. This study provides detailed illustrations based on existing facts and can assist further research using profitability, leverage, and capital intensity on tax avoidance.